2011
DOI: 10.1371/journal.pone.0027399
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of CXCR7 Expression Mediated by TLR4 Promotes Tumor Cell Proliferation and Migration in Human Colorectal Carcinoma

Abstract: The link between inflammation and colorectal carcinoma has been acknowledged. However, the impact of bacterial lipopolysaccharide (LPS) binding to Toll-like receptor 4 (TLR4) on chemokine receptors in human colorectal carcinoma cells still remains to be elucidated. The present study shows that exposure to LPS elevated CXC chemokine receptor 7 (CXCR7) expression in colorectal carcinoma SW480 and Colo 205 cell lines expressing TLR4/myeloid differential protein (MD-2). CXCR7 is associated with SW480 cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 25 publications
3
54
0
Order By: Relevance
“…40 IHC staining was independently examined by two clinical pathologists who were unaware of the patient outcome. Interpretation and evaluation of IHC results was as described previously.…”
Section: Ihc Interpretation and Evaluation Of Ihc Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 IHC staining was independently examined by two clinical pathologists who were unaware of the patient outcome. Interpretation and evaluation of IHC results was as described previously.…”
Section: Ihc Interpretation and Evaluation Of Ihc Resultsmentioning
confidence: 99%
“…Interpretation and evaluation of IHC results was as described previously. 40 Cell migration assay Twenty four-well transwell insert chambers (Merck KgaA, Darmstadt, Germany) were used for cell migration assy. One lakh cells (serum-starved overnight and then treated with or without GW9508 for 72 h before the assay) were added to the top chambers in serum-free medium (200 ml), and the bottom chambers were filled with medium containing 10% FBS.…”
Section: Ihc Interpretation and Evaluation Of Ihc Resultsmentioning
confidence: 99%
“…Since then, numerous studies have been conducted to investigate the effects of LPS on tumors. Several studies on tumor cell lines showed that TLR4 stimulation facilitates cell proliferation (4,5). Similarly, LPS facilitates carcinogenesis in mouse models of skin cancer (6), lung cancer (7), breast cancer (8), and colon cancer (9).…”
mentioning
confidence: 99%
“…LPS-induced inflammation activates TLR4 that in turn induces CXCR4 and/or CXCR7 expression in tumor cells, enhancing the response to CXCL12 to promote invasion and cell dissemination. 19 LPS exposure induced CXCR7 expression in human colon cancer cell lines SW480 and Colo 205 expressing TLR4/myeloid differential protein (MD-2). 19 Moreover, N15P polypeptide, a new CXCR4 antagonist derived from the Kaposi sarcoma secreted cytokine vMIP-II reversed the LPS-induced inflammation in human PBMC.…”
Section: Introductionmentioning
confidence: 99%
“…19 LPS exposure induced CXCR7 expression in human colon cancer cell lines SW480 and Colo 205 expressing TLR4/myeloid differential protein (MD-2). 19 Moreover, N15P polypeptide, a new CXCR4 antagonist derived from the Kaposi sarcoma secreted cytokine vMIP-II reversed the LPS-induced inflammation in human PBMC. 20,21 Targeting PD-1 T-cell coreceptor and its ligand B7-H1/ PD-L1 induce durable tumor responses 22 nevertheless only a minority of patients respond, and it has been unclear which patients and which tumors are the best candidates for this therapy.…”
Section: Introductionmentioning
confidence: 99%